CONCEPTION OF THE SCHOOL WORKROOM AND TECHNICAL FACILITIES AT CONTEMPORARY PARADIGM OF TECHNOLOGY - TVARŮŽKA, Václav (Trends in education, 2020)
The paper deals with the ideal facilities for technological education from the contemporary possibilities and perspectives´ point of view. The author proceeds from his pedagogical practice in condition of primary school. There was a special wing of the school building fully used due to its spatial and technical facilities. The paper deals with a workroom equipment from the contemporary trends of education´s point of view in developed countries.
Keywords: practical activities; technical and vocational education; technology; small material